PENINGKATAN PERKEMBANGAN SOSIAL MELALUI PETAK BENTENG USIA 5-6 TAHUN TK CITA SAHABAT MULIA PONTIANAK - Mardiyanti, Mardiyanti; Ali, Muhamad; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis research is motivated by a lack of social development in children aged 5-6 years in a class of 12 people with 2 teachers. This study aims to improve children's social development through playing petak benteng game in 5-6 year olds at Cita Sahabat Mulia Kindergarten, Pontianak. Good social development is very important for every child to be able to interact and be accepted in their social environment, therefore it is necessary to improve children's social development from an early age. This research is a Classroom Action Research. The subjects in this study were 5-6 years old at TK Cita Sahabat Mulia Pontianak. This research variable is the social development of children. Data collection through observation and interviews. The data analysis technique was carried out descriptively. The stages of this research consisted of planning, implementing, observing and reflecting. This research was conducted in 2 cycles. The results showed that the social development of children can improve after the action. The action taken is playing the petak benteng. The social development of the child develops in the aspect of the child being able to cooperate with friends reaching 100%, the aspect of the child being able to respect others up to 100%, and the aspect of the child being able to obey the agreed rules reaching 92% in the second cycle of meeting 2.Thus the child's social development can be improved through play petak benteng activities.Keywords: Social Development, Method of Petak Benteng Game